1990
DOI: 10.21273/hortsci.25.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate and Ammonium Leaching Losses from N Fertilizers Applied to `Penncross' Creeping Bentgrass

Abstract: Combining frequent N applications and irrigations for turfgrasses grown in sandy soils is a common occurrence on golf course putting greens. A greenhouse study was conducted to determine leaching losses of nitrate and ammonium nitrogen from `Penncross' creeping bentgrass (Agrostis palustris L.) growing on an 80 sand:20 peat soil mixture following frequent, moderately heavy irrigations and light or moderate N fertilizer applications. Nitrogen sources included calcium nitrate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
28
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 0 publications
4
28
0
Order By: Relevance
“…Nitrate‐N losses from hybrid bermudagrass were greatest from plots fertilized with AN, followed, in order, by UF, Milorganite, UF and IBDU (Brown et al, 1982). In other work, total leaching losses (NO 3 –N and ammonium) were <0.5% of applied N, regardless of the N source (calcium NO 3 –N, AN, ammonium sulfate, urea, UF, or IBDU) (Mancino and Troll, 1990).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Nitrate‐N losses from hybrid bermudagrass were greatest from plots fertilized with AN, followed, in order, by UF, Milorganite, UF and IBDU (Brown et al, 1982). In other work, total leaching losses (NO 3 –N and ammonium) were <0.5% of applied N, regardless of the N source (calcium NO 3 –N, AN, ammonium sulfate, urea, UF, or IBDU) (Mancino and Troll, 1990).…”
mentioning
confidence: 87%
“…When N rate was evaluated, loss of NO 3 –N from fertilized turfgrass was most often detected when excessive rates (3–6× the recommended rate) were applied (Rieke and Ellis, 1974; Brown et al, 1982; Mancino and Troll, 1990), a high rate of water soluble fertilizer was applied to a mature stand of turfgrass (Frank et al, 2006) or during turf establishment (Geron et al, 1993; Easton and Petrovic, 2004). Significant NO 3 –N leaching was not detected when N was applied at recommended rates for the turf species Kentucky bluegrass, St. Augustinegrass, and tall fescue (Miltner et al, 1996; Gross et al, 1990; Erickson et al, 2001, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that much of the N applied at lower rates of N application was being utilized by the growing turfgrass plants. It has been shown that inorganic N is rapidly used by growing turf (Allen et al, 1978;Mancino and Troll, 1990) and, in some cases, depleted within 2 to 4 d, primarily by biological immobilization (Bowman et al, 1989).…”
Section: Kcl Extractable Nh 4 -N and No 3 -Nmentioning
confidence: 99%
“…It has been reported that the NO 3 –N leaching losses from cool‐season turf are higher with soluble N formulations than with slow‐release formulations (Nelson et al, 1980; Mosdell and Schmidt, 1985; Sheard et al, 1985; Petrovic et al, 1986; Mancino and Troll, 1990; DeNobili et al, 1992; Geron et al, 1993; Engelsjord and Singh, 1997). Other factors in addition to N solubility will affect the leaching potential from turf and these include, but are not limited to, soil type, irrigation rate, N‐application rate, frequency and timing of fertilizer applications, stand density, rooting characteristics, and plant N demands (Petrovic, 1990).…”
mentioning
confidence: 99%